BODY STRUCTURE AND COMPOSITION OF CANOEISTS AND KAYAKERS: ANALYSIS OF JUNIOR AND TEENAGE POLISH NATIONAL CANOEING TEAM - M Hagner-Derengowska; W Hagner; IZ Zubrzycki; H Krakowiak; W Słomko; M Dzierżanowski; A Rakowski; M Wiącek-Zubrzycka (Termedia Publishing House, 2015)
The somatic build, biological age, general state of health, mental predisposition and physical fitness are the criteria for selection of individuals in competitive sport. The present study aims to analys the differences in body structure and composition of canoeists and kayakers and derive conclusions regarding the criteria for selection of individuals incompetitive sport. The research was conducted on a group of 32 men aged between 17 and 22: 16 kayakers and 16 Canadian canoeists of the junior and teenage Polish national canoeing team. Body composition was examined by means of bioelectrical segmental impedance. Body build type was determined using the anthropometric Heath-Carter method. Statistical analysis was performed using the Welch t-test. The examination of morphological features reveals significant differences in the studied parameters between the canoeists and kayakers. There are also significant differences between competitors of the Sydney 2000 Olympic Games and the studied group. We found that competitive kayakers should be taller than canoeists. The lower part of the body in kayakers is more developed than in canoeists and canoeists are more dehydrated than kayakers.